Etude Sedimentologique Et Stratigraphique Du Remplissage Du Premier Etage Du Gisement De Montgaudier, Charente, France - Mohammed, Boukhir; Abdel-Ali, Chaouni; Abderrahim, Lahrach (European Scientific Journal, ESJ, 2017)
The study of the deposits accumulated over time in the first stage of the Montgaudier site, at the level of the two sectors, confirmed that these sediments were non-native and were put in place by runoff. Concretion processes have transformed the sandy sediments from the western part of this filling into a sandy bank. The detailed granulometric analyzes of these deposits have made it possible to establish the palaeoclimatic factors, rather temperate and humid, which presided over them. These factors were defined by the shiny bluntness of the quartz grains of these sediments. Finally, the sediment stratigraphy of the two sectors and their correlation with the deposits of the Gaudry shelter allowed the establishment of a relative chronology of this filling.